Identification of A Liverwort Fossil on Pottery from A Church Excavation in Northern Sudan: Evidence for Moist Paleoenvironment - Ahmed, Ikram M.; Tahir, Yahia F.; Tomsah, Ibrahim I.; Ali, Ibrahim E. (Science Journal of University of Zakho, 2020)
This paper aims to document the first record of coalified compression fossil of a liverwort on pottery from a church excavation in the desert, northern Sudan. The outline or surface feature of the fossil is clearly observed. Morphological distortion is minimal while the internal anatomy is not preserved. The shapes of the archaeological specimens are closely similar to the morphology of a Riccia sp collected from the Red Sea state and the Blue Nile bank in Khartoum state. Energy-Dispersive X-ray fluorescence (EDXRF), Scanning Electron Microscopy with Energy (SEM/EDS), and Gas Chromatography and Mass Spectroscopy (GC-Mass) analytical techniques were used to determine the chemical composition of the fossil materials. Higher concentrations were reported for Carbon and Oxygen indicating the organic nature of the materials and also excluded the presence of manganese dentrites which perfectly imitate liverwort fossils. Also n-hexadecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, methyl ester, cis-9-hexadecenoic acid, 9, 12-octadecadienoic acid (z,z)-, methyl ester,tert-butyldimethylsilyl decanoic acid  were recorded for the fossil  materials. This study also provides additions to the chemical profile for the fresh material from the same genus which provides important data or monitors for the assessment of the chemical or thermal alteration in the corresponding coalified compression fossil.
Keywords: Liverwort, fossil, church excavation, desert, Sudan